Students' Creative Thingking Ability in view From The Level of Understanding in Waste Management - Zahrah, Syarifah; Retnowati, Rita; Istiana, Rita (Universitas Muhammadiyah Surakarta, 2023)
Creative Creative thinking is an important nature in the learning process, the weak ability of students' creative thinking is caused by a static learning process. This study aims to analyze the factors that cause high and low students' creative thinking abilities in terms of their level of understanding and identify other factors that influence creative thinking abilities. The subjects of this study were students of class XI MIPA at SMAN 1 Ciomas, Bogor Regency. The research was conducted in November 2022 – May 2023. The method used in this study was a mixed method with a sequential explanatory research design. The research sample was 123 students, the sampling technique used proportional random sampling technique. Quantitative data analysis techniques use descriptive and inferential analysis or hypothesis testing, namely correlation and regression, and qualitative data analysis techniques include data reduction, data presentation and drawing conclusions. The instrument used for Y and X variables is a multiple choice test instrument and for qualitative use interview guidelines, observation and documentation studies. The results showed that there was a fairly high positive correlation, with an r² value of 24.1%, students' creative thinking ability was influenced by understanding and the remaining 75.9% was influenced by internal factors including interests, hobbies and external factors including teacher guidance, environment, and some school activities. such as organization, performing arts, social media. The solution to overcome these problems is to develop learning designs for environmental materials that can increase understanding so that students are better trained to have the ability to think creatively in solving environmental problems. The existence of collaboration between schools in developing learning designs can increase understanding so that students have the ability to think creatively.